Addressing HIV stigma in healthcare, community, and legislative settings in Central and Eastern Europe - Ana-Maria Schweitzer; Arian Dišković; Veronica Krongauz; Julie Newman; Janez Tomažič; Nina Yancheva (AIDS Research and Therapy, 2023)
Abstract Introduction Surging HIV prevalence across countries of Central and Eastern Europe (CEE) is largely a result of poor HIV care engagement and a lack of comprehensive support for key populations. This is fostered by widespread stigma across healthcare, community, and legislative settings. Discussion Throughout CEE, HIV stigma and intersectional stigma are serious obstacles to providing adequate medical care to people living with HIV. Anticipated and enacted (experienced) stigma from healthcare professionals, and fears of breaches in confidentiality, deter individuals from having an HIV test and engaging in HIV care. Furthermore, negative connotations surrounding HIV infection can lead to discrimination from family, friends, colleagues, and the public, leading to internalized stigma and depression. Key populations that have higher HIV prevalence, such as men who have sex with men, people who inject drugs, transgender individuals, and sex workers, experience additional stigma and discrimination based on their behaviour and identities. This contributes to the concentrated HIV epidemics seen in these populations in many CEE countries. The stigma is exacerbated by punitive legislation that criminalizes HIV transmission and penalizes sexual orientation, drug use, gender identities, and sex work. Despite high levels of HIV stigma and intersectional stigma, there are many evidence-based interventions that have reduced stigma in other parts of the world. Here, we discuss the interventions that are currently being enacted in various countries of CEE, and we suggest additional effective, evidence-based interventions that will tackle stigma and lead to increased HIV care engagement and higher rates of viral suppression. We cover the promotion of the undetectable = untransmittable (U = U) message, stigma-reduction education and training for healthcare professionals, patient-centric approaches for testing and treatment, and advocacy for non-discriminatory legislation, policies, and practices. We also consider targeted stigma-reduction interventions that acknowledge the wider challenges faced by marginalized populations. Conclusions HIV stigma and intersectional stigma in CEE drive poor engagement with HIV testing services and care. Widespread adoption of evidence-based interventions to tackle stigma highlighted in this review will improve the quality of life of people living with HIV, improve HIV care engagement, and ultimately slow the surging HIV prevalence and concentrated epidemics occurring throughout CEE.